The blue ribbon brides collection : 9 historical women win more than a blue ribbon at the fair - Pagels, Carrie Fancett; Breidenbach, Angela; Franklin, Darlene; Welborn, Gina.; AlLee, Jennifer; Whitham, Becca; Turner, Niki.; Stockton, Amber; Hickey, Cynthia (Barbour Books, 2016)
Visit state and county fairs between 1889 and 1930, and join nine men and women who are going for big prizes-that just might lead to love. Includes recipes.
Requilted with love / Carrie Fancett Pagels -- Seven medals and a bride / Angela Breidenbach -- A taste of honey / Darlene Franklin -- Altered hearts / Gina Welborn -- Better with butter / Jennifer AlLee -- Driven to distraction / Becca Whitham -- First comes pie / Niki Turner -- Front Paige love / Amber Stockton -- Competing hearts / Cynthia Hickey.
Anthology.
Keywords: Agricultural exhibitions -- Fiction; Agriculture -- Competitions -- Fiction; Romance fiction, American; Historical fiction, American; Christian fiction, American; FICTION / Christian / Romance; Agricultural exhibitions; Agriculture -- Competitions; Christian fiction, American; Historical fiction, American; Romance fiction, American; Christian fiction; Christian fiction; Fiction; Historical fiction; Novellas; Romance fiction; Christian fiction; Romance fiction; Historical fiction; Novellas